Adhesive and hydrophobic properties of Escherichia coli from the rectal mucosa of patients with ulcerative colitis. - Hartley, M G (1993)
The adherent properties and hydrophobicity of Escherichia coli isolates have been compared from the rectal mucosa of patients with active and inactive ulcerative colitis and from a control patient group. Patients with active colitis were colonised less frequently and with lower numbers of E coli than were control patients. Mannose resistant adhesion to HEp-2 cells was determined for 124 isolates of E coli and surface hydrophobicity was estimated by salt agglutination in 96 of these isolates. There was no significant difference in the distribution of adherent strains between the colitis patient groups or with disease activity. E coli from the control patients were marginally less adhesive than those from colitics. The hydrophobicity of isolates did not differ significantly between colitic and control groups nor were there significant differences correlated with disease activity. Furthermore, for these mucosal E coli isolates, hydrophobicity and mannose resistant adhesion were unrelated characteristics.